Beyond Moiré with Spatial Frequency Mastery via δ‐Function Expansion Metasurface - Rongsheng Chen; Feilong Yu; Jin Chen; Rong Jin; Jie Wang; Jiuxu Wang; Xiaoshuang Chen; Wei Lu; Guanhai Li (Advanced Science)
Abstract Mastering spatial frequency manipulation within momentum space is pivotal yet challenging, particularly in mitigating moiré patterns that significantly impair image quality across diverse applications. Conventional methods often require trade‐offs in spatial resolution or fall short of completely eradicating unwanted frequencies, further burdened by complex post‐processing demands. In this work, a novel coherent δ‐function expansion technique implemented through an all‐silicon metasurface, affording unparalleled synergistic control over arbitrarily selected spatial frequencies via refined k‐space amplitude and phase modulations is introduced. This approach transcends traditional global methods by harnessing a sophisticated ensemble of multiple δ‐functions, enabling a holistic manipulation of spatial frequencies. The periodicity introduced by this approach also enables the feasibility of infinitely spatial stitching expansion for metasurfaces while maintaining high energy utilization efficiency. The methodology excels in the meticulous removal of local moiré frequencies while concurrently facilitating numerous advanced optical functions, including mixed partial differentiation and noise suppression, all within the optical domain. This work heralds a significant leap forward in optical manipulation, presenting a viable, scalable alternative to complex electronic post‐processing. Through this work, not only a longstanding challenge is addressed in optical physics but also open new avenues for research and application in photodetection and optical processing technologies.